(untitled) (Historia, 2021)
In this brief autobiography of Botswana’s late and former vice president, Mompati Sebogodi Merafhe, the author chronicles his life story which began in Serowe in 1936. Like most Batswana at the time, his parents were peasants and he looked after the family livestock before attending primary school in Serowe. Merafhe claims that he was a brilliant student with an admirable flair for the English language which other pupils were encouraged to emulate. However, owing to family commitments, his academic potential could not be fully realised and he ended his schooling at a lowly standard 6 level. Thereafter, he joined the colonial police force in 1960 in Gaborone. Merafhe’s first posting was in the intelligence unit called the Special Branch. He says its prying and intrusive nature put him off so much that he asked to be transferred elsewhere and he was then shifted to the paramilitary Police Mobile Unit (PMU) in late 1960. Soon he also left the PMU and was transferred to Lobatse Police Station.